Sistem Monitoring Security Building Berbasis E-KTP dan NodeMCU ESP8266 - Faahmi, Muh. Kharis; Nawawi, Ibrahim; Yuliantari, Risky Via (Politeknik Negeri Batam, 2024)
This article discusses a building security monitoring system based on the Internet of Things (IoT), designed to monitor the main door using the MQTT (Message Queuing Telemetry Transport) protocol, a technology that enables long-distance data transmission with very low power consumption. The main advantage of this system is its energy efficiency, making it ideal for security applications that require long-term monitoring without draining resources. The system works by collecting data from sensors installed on the main door and sending it to a web server, where the data is stored and can be monitored in real-time by users. This allows building managers to quickly detect and respond to potential security threats, such as unauthorized access or disturbances at the main door. In addition to providing accurate monitoring, the system also offers reliable protection, enhancing the overall security of the building. The ability to respond quickly to threats makes this system an effective and dependable security solution for safeguarding property.